Pengaruh Media Linimasa Sejarah Card Game terhadap Minat Belajar Sejarah Siswa di SMAN 2 Kota Binjai Sumatera Utara - *Yoga Tri Nugraha; Teuku Kusnafizal; Muhjam Kamza (Universitas Syiah Kuala, 2022)
This research was motivated by the low interest in learning students in history subjects in class XI IS at SMAN 2 Binjai City, North Sumatra. The purpose of this study is to determine the influence of card game history timeline media on the interest in learning history of class XI IS students at SMAN 2 Binjai City, North Sumatra and the magnitude of the influence of Card Game History Timeline media on the interest in learning history of class XI IS students at SMAN 2 Binjai City, North Sumatra. This research uses a quantitative approach with a type of true experimental design research using posttest-only control design. The population in this study was all class XI IS students at SMAN 2 Binjai City which amounted to 4 classes and the sample used in this study was class XI IS 3 as a control class consisting of 20 students and class XI IS 4 as an experimental class consisting of 20 students. Sampling technique using simple random sampling. The data collection technique in this study used observation, documentation, and questionnaire provision. Based on the results of the study, it is known that the results of the hypothesis test used a t-test and obtained a calculated value = 1.40, while ttabel = 1.31 at a significant level (α = 0.05) while dk = 38 was 1.31 with the criteria Ha accepted.